Omega-3 Polyunsaturated Fatty Acids and Stroke Burden - Yuji Ueno; Nobukazu Miyamoto; Kazuo Yamashiro; Ryota Tanaka; Nobutaka Hattori (International Journal of Molecular Sciences, 2019)
Stroke is a major leading cause of death and disability worldwide. N-3 polyunsaturated fatty acids (PUFAs) including eicosapentaenoic acid and docosahexaenoic acid have potent anti-inflammatory effects, reduce platelet aggregation, and regress atherosclerotic plaques. Since the discovery that the Greenland Eskimo population, whose diet is high in marine n-3 PUFAs, have a lower incidence of coronary heart disease than Western populations, numerous epidemiological studies to explore the associations of dietary intakes of fish and n-3 PUFAs with cardiovascular diseases, and large-scale clinical trials to identify the benefits of treatment with n-3 PUFAs have been conducted. In most of these studies the incidence and mortality of stroke were also evaluated mainly as secondary endpoints. Thus, a systematic literature review regarding the association of dietary intake of n-3 PUFAs with stroke in the epidemiological studies and the treatment effects of n-3 PUFAs in the clinical trials was conducted. Moreover, recent experimental studies were also reviewed to explore the molecular mechanisms of the neuroprotective effects of n-3 PUFAs after stroke.